2015
DOI: 10.1182/blood-2014-12-580001
|View full text |Cite
|
Sign up to set email alerts
|

Inherited genetic variation in childhood acute lymphoblastic leukemia

Abstract: Although somatically acquired genomic alterations have long been recognized as the hallmarks of acute lymphoblastic leukemia (ALL), the last decade has shown that inherited genetic variations (germline) are important determinants of interpatient variability in ALL susceptibility, drug response, and toxicities of ALL therapy. In particular, unbiased genome-wide association studies have identified germline variants strongly associated with the predisposition to ALL in children, providing novel insight into the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
98
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 108 publications
(82 reference statements)
2
98
0
1
Order By: Relevance
“…Recent genome-wide association studies have shown certain single nucleotide polymorphisms in genes like ARID5B, IKZF1, CEBPE, CDKN2A, PIP4K2A, and GATA3 to be associated with an increased risk for developing ALL. 8 However, these findings do not account for the vast majority of cases.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 92%
“…Recent genome-wide association studies have shown certain single nucleotide polymorphisms in genes like ARID5B, IKZF1, CEBPE, CDKN2A, PIP4K2A, and GATA3 to be associated with an increased risk for developing ALL. 8 However, these findings do not account for the vast majority of cases.…”
Section: Acute Lymphoblastic Leukemiamentioning
confidence: 92%
“…The genetic landscape produced by inherited germline variations contributes to leukemogenesis and disease outcome, 31 and is a biological component that contributes to racial, ethnic and other health disparities in ALL. 32 This is particularly relevant in CRLF2 B-ALL which occurs five times more often in Hispanic children than others 28 and comprises more than half of the ALL cases in children with Down Syndrome.…”
mentioning
confidence: 99%
“…High-risk Ph-like ALL is especially important since it is characterized by tyrosine kinase activation that can be inhibited with currently available pharmacological agents [4,5]. Genomic profiling has also aided identification of inherited risk factors for leukaemia development including GATA3, IKZF1, CEBPE and CKDN2A [6].…”
Section: Dear Readersmentioning
confidence: 99%